2011
DOI: 10.1007/s12519-011-0324-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of childhood obesity treatment on body composition and metabolic profile

Abstract: Obesity-related metabolic risk factors reduced in prepubertal children if BMI-SDS decreased substantially. This result was not dependent on which intervention, family-oriented group program or routine counselling, was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
12
0
3
Order By: Relevance
“…In the present study, there was a signi cant improvement in body composition at 12 months of follow-up in the BG, particularly in the fat mass index. In a randomized study with obese children aged seven to nine years old which aimed to compare the impact of a program of 14 group sessions with a program of two routine counselling consultations in body composition and metabolic pro le, the authors found higher decreases of fat mass (kg) in the group program children, with a decrease of BMI z-score greater than or equal to 0,25 [25]. These results corroborate those obtained in the present study, where there was a greater decrease in fat mass (kg) after 12 months follow-up in the BG than in the STG.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was a signi cant improvement in body composition at 12 months of follow-up in the BG, particularly in the fat mass index. In a randomized study with obese children aged seven to nine years old which aimed to compare the impact of a program of 14 group sessions with a program of two routine counselling consultations in body composition and metabolic pro le, the authors found higher decreases of fat mass (kg) in the group program children, with a decrease of BMI z-score greater than or equal to 0,25 [25]. These results corroborate those obtained in the present study, where there was a greater decrease in fat mass (kg) after 12 months follow-up in the BG than in the STG.…”
Section: Discussionmentioning
confidence: 99%
“…Die Reduktion der metabolischen Veränderungen steht dabei in direktem Zusammenhang mit der erreichten Gewichtsreduktion. Eine Verringerung des BMI-SDS um 0,5 Einheiten führt zu einer Verbesserung aller Komponenten des metabolischen Syndroms [33,49]; eine Verringerung um mind. 0,25 BMI-SDS Einheiten bewirkt bereits eine Reduzierung des Nüchterninsulins [33].…”
Section: Bewegungunclassified
“…One arm of an intervention took place in a high school [33] and one arm of an intervention took place in a school health center [43, 44]. Another intervention had one arm that included an inpatient component [55].…”
Section: Review Processmentioning
confidence: 99%
“…Another intervention had one arm that included an inpatient component [55]. For some approaches, interventions extended beyond clinic walls and involved phone coaching [3032, 37, 48], text messaging [48], telemedicine [24], home visits [17,47, 48, 57, 58] and communication with families via newsletters, manuals, automated phone, and educational audio tapes [22, 25, 30, 32, 35, 37, 40, 44, 61]. …”
Section: Review Processmentioning
confidence: 99%